Test Performance Related Dysfunctional Beliefs - Recep TÜTÜNCÜ; Ahmet İNCE; M. Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Examinations by using tests are very frequently used in educational settings and successful studying before the examinations is a complex matter to deal with. In order to understand the determinants of success in exams better, we need to take into account not only emotional and motivational, but also cognitive aspects of the participants such as dysfunctional beliefs. Our aim is to present the relationship between candidates’ characteristics and distorted beliefs/schemata just before an examination. Method: The subjects of the study were 30 female and 30 male physicians who were about to take the medical specialization exam (MSE) in Turkey. Dysfunctional Attitude Scale (DAS) and Young Schema Questionnaire Short Form (YSQ-SF) were applied to the subjects. The statistical analysis was done using the F test, Mann-Whitney, Kruskal-Wallis, chi-square test and spearman’s correlation test. Results: It was shown that some of the DAS and YSQ-SF scores were significantly higher in female gender, in the group who could not pass the exam, who had repetitive examinations, who had their first try taking an examination and who were unemployed at the time of the examination. Conclusion: Our findings indicate that candidates seeking help before MSE examination could be referred for cognitive therapy or counseling even they do not have any psychiatric diagnosis due to clinically significant cognitive distortion. Measurement and treatment of cognitive distortions that have negative impact on MSE performance may improve the cost-effectiveness and mental well being of the young doctors.